1970
DOI: 10.2307/3211948
|View full text |Cite
|
Sign up to set email alerts
|

On the distribution and moments of the strength of a bundle of filaments

Abstract: SummarySmall sample and large sample properties of the bundle strength of parallel filaments studied earlier by Daniels (1945) and Sen, Bhattacharyya, Suh (1969) have been developed here by probabilistic argument. The statistics belong to a family or class of statistics, each of which forms a reverse semi-martingale sequence. Certain moment properties are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Proof. The proof is a straightforward extension of the method of Suh, Bhattacharyya, and Grandage (1970) for equal load sharing. Let E. for i in S denote the event that fiber i has strength at most XA i (S) and the system S fails under load x.…”
Section: Parallel Systems Of Fibersmentioning
confidence: 98%
See 1 more Smart Citation
“…Proof. The proof is a straightforward extension of the method of Suh, Bhattacharyya, and Grandage (1970) for equal load sharing. Let E. for i in S denote the event that fiber i has strength at most XA i (S) and the system S fails under load x.…”
Section: Parallel Systems Of Fibersmentioning
confidence: 98%
“…which is equivalent to Equation (2.6) of Suh et al (1970) rewritten in terms of load per fiber instead of total load. The formula is originally due to Daniels (1945).…”
Section: Parallel Systems Of Fibersmentioning
confidence: 99%
“…In a well combed and brush~d fiber bundle, assumptions 1 and 2 should hold; assumption 3 is widely accepted for cotton fibers; assumption 4 on the independence of fiber tensile properties is essential for simplifying model development; and assumption 5 is made because small bundle properties are quite complex and nonlinear with respect to the number of fibers in the bundle, whereas they quickly approach asymptotic limits as the bundle size becomes sufficiently large [ 19]. These assumptions provide much simplification for studying a large fiber bundle and its tensile behavior.…”
Section: Theorymentioning
confidence: 99%
“…Theoretical studies on the tensile behavior of straight fiber bundles can also be found in papers by Daniel [?., 3], Platt~ 15). Coleman 111, Suh [ 18,19], Phoenix [10][11][12][13], Duckett 141. and Pitt [ 14]. Extensive experimental work on straight fiber bundles has been reported by several researchers 17, 15,16,23].…”
mentioning
confidence: 99%
“…Theoretical studies on the tensile behavior of ideal (straight) fiber bundles were also completed by Daniels [5], Coleman [3], Suh et al [28], Duckett [91, Phoenix . I , 876 [ 19,22], and Pitt [23].…”
mentioning
confidence: 99%